Diversity of phyllophagous organisms on woody plants in the Botanical garden in Nitra, Slovakia (Acta Entomologica Serbica, 2013)
This paper deals with identification of phyllophagous organisms colonizing various woody plant species in the Botanical Garden of the SUA (Slovak University of Agriculture). The research was carried out from 2010 to 2012 and the field work took place at two week intervals during the growing season. The main objective was to determine and evaluate the phyllophagous pests according to host plants. Adults, larvae of pests and damaged leaves were collected in a specified locality and documented by herbal samples and macrophotos. The occurrence of non-native insect pests was observed as well. During the research taxa of 108 species of phyllophagous pests on 48 woody plants were recorded. As the results indicate, the most phyllophagous insect species were found on Quercus (16), Acer (12), and Betula (11). The largest number of insect species belongs to the families Lepidoptera (49) and Hemiptera (17). Concerning the alien pests, 10 phyllophagous species were identified. These were Phyllonorycter platani (Staudinger, 1870), Phyllonorycter issikii (Kumata, 1963), Phyllonorycter leucographella (Zeller, 1850), Cameraria ohridella (Deschka & Dimic 1986), Monarthropalpus flavus (Schrank, 1776), Dasineura gleditsiae (Osten Sacken, 1866), Corythuca ciliata (Say, 1832), Aceria erinea (Nalepa, 1891), Aceria pyracanthi (G. Canestrini, 1891) and Aphis craccivora (Koch, 1854). A list of all recorded phyllophagous species in the Botanical Garden is mentioned in Tab. I.